2022
DOI: 10.1371/journal.pmed.1003905
|View full text |Cite
|
Sign up to set email alerts
|

Ruling out pulmonary embolism across different healthcare settings: A systematic review and individual patient data meta-analysis

Abstract: Background The challenging clinical dilemma of detecting pulmonary embolism (PE) in suspected patients is encountered in a variety of healthcare settings. We hypothesized that the optimal diagnostic approach to detect these patients in terms of safety and efficiency depends on underlying PE prevalence, case mix, and physician experience, overall reflected by the type of setting where patients are initially assessed. The objective of this study was to assess the capability of ruling out PE by available diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 30 publications
0
31
0
7
Order By: Relevance
“…A recent systematic review compared the capacity of ruling out PE among the Wells, Geneva, YEARS, and PERC scores across different healthcare settings. In the hospitalized healthcare setting, the Wells plus PTP-adjusted D-dimer(sensitivity 95.64%, specificity 39.50%), the Geneva plus PTP-adjusted D-dimer(sensitivity 95.73%, specificity 37.29%), and the YEARS plus PTP-adjusted D-dimer(sensitivity 96.94%, specificity 35.83%) yielded similar diagnostic accuracy [ 27 ]. It was basically consistent with the present results, except that the YEARS was inferior to the other two in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review compared the capacity of ruling out PE among the Wells, Geneva, YEARS, and PERC scores across different healthcare settings. In the hospitalized healthcare setting, the Wells plus PTP-adjusted D-dimer(sensitivity 95.64%, specificity 39.50%), the Geneva plus PTP-adjusted D-dimer(sensitivity 95.73%, specificity 37.29%), and the YEARS plus PTP-adjusted D-dimer(sensitivity 96.94%, specificity 35.83%) yielded similar diagnostic accuracy [ 27 ]. It was basically consistent with the present results, except that the YEARS was inferior to the other two in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Ever since the Wells and Geneva score emerged, their role in the PTP prediction of PE have been externally validated in a series of previous studies [ 2 , 6 , 9 , 27 , 37 ]. The Geneva and Wells have the most(30 times) and third most(28 times) presence frequency of VTE risk elements, as well as highest(4.29) and second highest(4.00) presence frequency per element among all these six scores, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Da die PERC Regel in der Literatur teilweise kritisiert wird und in der ESC-Leitlinie bisher keine generelle Empfehlung ausgesprochen wurde [6], wenden wir die PERC-Regel ausschließlich bei Patient:innen mit klinisch sehr niedriger Wahrscheinlichkeit an. Wird die Wahrscheinlichkeit mithilfe des WELLS-Scores bestimmt, empfehlen wir einen konservativen Wert <2 Punkten (Hinweis: in der Literatur erfolgt die Anwendung der PERC-Regel teilweise bis zu einem WELLS-Score von <5 Punkten [14]).…”
Section: Perc-regelunclassified
“…These patients typically reflect more severe and progressive illness with a high VTE risk. As recently highlighted by an individual participant data meta-analysis (IPD-MA), including over 35,000 patients suspected of PE across different healthcare settings, it is relevant to take PE-prevalence in consideration when judging the performance of the different diagnostic strategies in settings with more high-risk patients [ 43 ]. The IPD-MA showed that both failure rate (i.e., false negative result of test) and efficiency became poorer for all currently available diagnostic strategies.…”
Section: Diagnosis Of Acute Pe In Special Populationsmentioning
confidence: 99%